Instruments for Short-Term (24 h) Violence Risk Assessment and Strategies for Managing Violence Risk Among Adolescents With Risk for Violent Behaviour: A Systematic Review - Väätäinen, Laura; Björkqvist, Maiju; Li, Yan; Pelto-Piri, Veikko; Ferreira, António; Lantta, Tella (WILEY, 2026)
Short-term (24 h) violence risk assessment and management can reduce violence in institutional settings, yet they remain understudied in adolescent populations. This systematic review aimed to identify instruments used for short-term violence risk assessment and strategies for managing violence risk among adolescents in institutional settings, as well as to evaluate related outcomes. PRISMA was used as an evidence-based minimum set of items for reporting systematic reviews. The literature search (March 2024 and March 2025) was conducted in PubMed, PsycINFO, Web of Science, CINAHL, The Cochrane Library and Scopus, and references from selected studies were reviewed. Data extraction and analysis were performed in Covidence. Nine studies met inclusion criteria describing six assessment instruments: DASA, DASA-YV, V-RISK-Y, Kennedy Axis V, Pedi-BEWS and BVC. No studies regarding strategies for short-term violence risk management were identified. DASA-YV, BVC and V-RISK-Y predicted violence among adolescents within 24 h (AUC = 0.70-0.95); DASA predicted violence moderately (AUC = 0.50-0.69). Pedi-BEWS (ICC = 0.83) and Kennedy Axis V (ICC = 0.79) demonstrated similar inter-rater reliability. Due to the lack of studies, firm conclusions on the best instrument for clinical practice in institutional settings remained elusive. Further research is necessary to ascertain if youth-specific instruments (e.g., DASA-YV, V-RISK-Y) predict violence more effectively than non-age-specific instruments (e.g., DASA). The lack of youth engagement in violence risk assessment stands out clearly. Scoring was done by the staff, mostly by nurses. Future studies should involve adolescents in the scoring or evaluation of assessment and management. There is a need for evidence-based recommendations for youth engagement.